Decoding abstract and concrete concept representations based on single‐trial fMRI data. Issue 5 (16th January 2012) - Wang, Jing; Baucom, Laura B.; Shinkareva, Svetlana V.
Abstract Previously, multi‐voxel pattern analysis has been used to decode words referring to concrete object categories. In this study we investigated if single‐trial‐based brain activity was sufficient to distinguish abstract (e.g., mercy) versus concrete (e.g., barn) concept representations. Multiple neuroimaging studies have identified differences in the processing of abstract versus concrete concepts based on the averaged activity across time by using univariate methods. In this study we used multi‐voxel pattern analysis to decode functional magnetic resonance imaging (fMRI) data when participants perform a semantic similarity judgment task on triplets of either abstract or concrete words with similar meanings. Classifiers were trained to identify individual trials as concrete or abstract. Cross‐validated accuracies for classifying trials as abstract or concrete were significantly above chance (P < 0.05) for all participants. Discriminating information was distributed in multiple brain regions. Moreover, accuracy of identifying single trial data for any one participant as abstract or concrete was also reliably above chance (P < 0.05) when the classifier was trained solely on data from other participants. These results suggest abstract and concrete concepts differ in representations in terms of neural activity patterns during a short period of time across the whole brain. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.